Analysis of factors affecting compliance of health workers using personal protective equipment - Lamria Situmeang; Sulistiyani; Ni Komang Ayu Trianingsih; Kismiyati (Science Midwifery, 2023)
Compliance with the use of PPE in the workplace is an effort to minimize the risks that occur and as a form of guarantee of work safety and security when carrying out medical procedures. There are several factors that influence the adherence of health workers to using Personal Protective Equipment (PPE). The purpose of this study was to determine the factors that influenced the adherence of health workers to using Personal Protective Equipment (PPE) during the Covid-19 pandemic at the Waena Health Center. This type of research is quantitative with cross sectional design. The number of research samples was 51 respondents who were taken by simple random sampling technique. Data collection used questionnaires and observation sheets with the Fisher's Exact Test statistic. The Fisher Exact Test statistical test research showed that there was an effect of knowledge (p=0.027 <0.05), years of service (p=0.042 <0.05), and attitude (p=0.006 <0.05) and which had no effect on compliance of health workers using Personal Protective Equipment (PPE), namely the availability of PPE (p=1.000 > 0.05). Health workers should always be aware of the importance of using PPE to maintain personal safety when providing health services.